The Image of God and Prayer in the Statements of Young People Aged 15–19 from Southeastern Poland - Kielian, Andrzej (Religions, 2025)
This article aims to explore the image of God and prayer practices among young people aged 15–19 from southeastern Poland. The study was conducted between 2019 and 2020 using an online survey (CAWI) on a sample of 1171 students. Cluster and exploratory factor analysis identified three types of God images: transcendent, nature-based, and human construct. The results suggest that the image of God influences the frequency and context of prayer. Adolescents with a transcendent image of God pray more often in emotional contexts, such as gratitude or fear. The study also highlights the decreasing importance of traditional prayer rituals, suggesting a process of individualization of religiosity and the impact of secularization.